A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS SMA PGRI PEKANBARU IN COMPREHENDING NARRATIVE TEXT - Fitrin Hasmy; Syofia Delfi; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research objective is to find out the ability of the second year students SMA PGRI Pekanbaru in comprehending narrative text. The research data were collected in January 2017. The subject of this research was class XI MIPA 3 which has 40 students. The data were collected using reading comprehension test with multiple choice type. The test consisted of 40 items. The research result, it found out that the ability of the second year students’ in comprehending narrative text is in mediocre level with the mean score of 43.12. The students’ mean score in main idea is in mediocre level with the main score of 47.00. The students’ mean score in specific information is in mediocre level with the main score of 51.25. The students’ mean score in reference is in poor level with the main score of 28.00. The students’ mean score in inference is in mediocre level with the main score of 48.00. The students’ mean score in vocabulary is in mediocre level with the main score 45.75. The students’ mean score in social function is in poor level with the mean score of 28.00. As a conclusion, the highest score obtained by the students is in specific information with the mean score of 51.25 with categorized into mediocre level and the lowest score that the students got are in reference and social function with the mean score of 28.00 with categorized into poor level. Thus, it is recommended that the students need to get improvement to comprehend narrative texts.Keywords: reading comprehending, narrative text